Spa and Wellness Tourism in Slovakia (A Geographical Analysis) - Kasagranda Anton (Czech Journal of Tourism: Journal of Masaryk University, 2017)
Spa industry is presently an inherent part of Slovak tourism. For this reason, it has become a major interest of scientific and professional literature (economics, management, sociology, or geography). The main topic of this paper is the evaluation of tourism in Slovakia through a geographic analysis. This paper briefly evaluates the development and the importance of spa, spa tourism and wellness and their main research areas and issues. Furthermore, the primary sources of tourism development, the overview of spa tourism and the wellness resorts, the accommodation establishments and the visitation rate are evaluated as well. In conclusion, functional and spatial typification of spa tourism and wellness in Slovakia is presented. The structure of the paper is designed to be appropriate for a comparison with V4 countries.